DMSO-mediated palladium-catalyzed cyclization of two isothiocyanates via C–H sulfurization: a new route to 2-aminobenzothiazoles. Issue 6 (25th January 2019) - Yao, Guangkai; Wang, Bing-Feng; Yang, Shuai; Zhang, Zhi-Xiang; Xu, Han-Hong; Tang, Ri-Yuan
Abstract : DMSO-initiated coupling of two isothiocyanates; Pd-catalyzed C–H sulfurization. Abstract : DMSO was found to activate arylisothiocyanates for self-nucleophilic addition. A subsequent intramolecular C–H sulfurization catalyzed by PdBr2 enables access to a wide range of 2-aminobenzothiazole derivatives in moderate to good yields. This is the first example of a DMSO-mediated Pd-catalyzed synthesis of 2-aminobenzothiazoles through cyclization/C–H sulfurization of two isothiocyanates.